Climate change and plant health - Hoeschle-Zeledon, Irmgard (2011)
The discussion on the impact of climate change (CC) on agriculture has often focused on how changes in temperature, rainfall, and CO2 concentrations will affect the suitability of temperate regions for crop production and how crops will react in terms of yields. The effects of climate change on biotic factors in the tropics, such as weeds, pests, and pathogens (hereafter referred to as pests), have not received much attention.